2015
DOI: 10.3389/fphys.2015.00356
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Energy X-Ray Absorptiometry, Skinfold Thickness, and Waist Circumference for Assessing Body Composition in Ambulant and Non-Ambulant Wheelchair Games Players

Abstract: Field-based assessments provide a cost–effective and accessible alternative to dual-energy X-ray absorptiometry (DXA) for practitioners determining body composition in athletic populations. It remains unclear how the range of physical impairments classifiable in wheelchair sports may affect the utility of field-based body composition techniques. The present study assessed body composition using DXA in 14 wheelchair games players who were either wheelchair dependent (non-walkers; n = 7) or relied on a wheelchai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 30 publications
(54 reference statements)
2
35
0
Order By: Relevance
“…Comparing these results to the study of Keil et al (16), both studies showed similar results for fat mass and fat-free mass in the arms, legs and trunk in basketball players. The same was true for Willems et al (19) investigating body composition in 14 wheelchair games player. Additionally, they showed a significantly lower total lean tissue mass in non-walkers compared to walkers.…”
Section: Body Composition In Able-bodied and Disabled Athletesmentioning
confidence: 62%
See 1 more Smart Citation
“…Comparing these results to the study of Keil et al (16), both studies showed similar results for fat mass and fat-free mass in the arms, legs and trunk in basketball players. The same was true for Willems et al (19) investigating body composition in 14 wheelchair games player. Additionally, they showed a significantly lower total lean tissue mass in non-walkers compared to walkers.…”
Section: Body Composition In Able-bodied and Disabled Athletesmentioning
confidence: 62%
“…Several different studies investigated body composition in wheelchair athletes using the DXA method (6,15,16,(18)(19)(20). Most of these studies focused on one sports discipline, a gender or one lesion level (e.g., tetraplegia or paraplegia).…”
Section: Introductionmentioning
confidence: 99%
“…Lean et al and Durnin and Womersley equations underestimated %BF by 2.1% and 4.2% in non‐disabled and by 10.6% and 8.3% in disabled athletes while Lean et al equations overestimated %BF in post‐menopausal women . Durnin and Womerley equations have been shown to underestimate %BF in men and women and to underestimate %BF more as BMI increases from overweight to obese . Cui et al showed that equations that included skinfolds tended to underestimate %BF more in the adults with obesity than the non‐obese when applied to NHANES data .…”
Section: Discussionmentioning
confidence: 99%
“…The Lean et al equations developed in 16 to 65 year olds applied to youth 13 to 17 years resulted in estimates of %BF in men and women that were systematically low . Lean et al and Durnin and Womersley equations underestimated %BF by 2.1% and 4.2% in non‐disabled and by 10.6% and 8.3% in disabled athletes while Lean et al equations overestimated %BF in post‐menopausal women . Durnin and Womerley equations have been shown to underestimate %BF in men and women and to underestimate %BF more as BMI increases from overweight to obese .…”
Section: Discussionmentioning
confidence: 99%
“…Wheelchair basketball and the protrusion of the wheelchair itself may increase arm muscle volume. DEXA has been shown to be an effective tool in the evaluation of wheelchair basketball players [20,30]. The assessment of body composition, LBM, BFP, and BMI showed that individuals with spinal cord disorders and frequent wheelchair use had considerable differences with respect to the arms and legs.…”
Section: Discussionmentioning
confidence: 99%